Model Simulasi Dinamis Pengelolaan Sampah di Kabupaten Jepara Berbasis Stella - Adzkia Nur Nasution; Ardilla Syahfitri Lubis; Putri Harliana (LKP KARYA PRIMA KURSUS, 2025)
Waste management has become increasingly complex due to population growth and limited infrastructure, especially in densely populated areas such as Jepara Regency. To better understand this issue, this study employs a system dynamics approach to simulate waste generation projections up to the year 2030. The model was developed using 2023 baseline data and incorporates variables such as population growth, waste sorting effectiveness, and land area. The simulation was conducted using Stella, a specialized modeling software designed to visualize dynamic systems through flow diagrams and causal relationships. Stella enables users to explore how variables interact over time, making it a valuable tool for analyzing potential policy outcomes through scenario testing. The simulation results indicate that waste volume can be reduced if waste sorting policies are consistently implemented at the household level. This model provides a comprehensive overview of policy impacts and serves as a decision-support tool for strategic waste management planning at the regional level. The findings highlight the importance of data-driven planning to establish a sustainable and responsive waste management system in the face of changing demographic conditions.